Pemberdayaan Komunitas Pasar Regeng Yogyakarta melalui Pelatihan Komunikasi Interpersonal dan Storytelling Produk Ramah Lingkungan - Ni Luh Ketut Indah Widia Sari; Dianingtyas Murtanti Putri; Nadhifa Salsabila (Indonesian Journal for Social Responsibility, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role as the backbone of Indonesia’s economy, contributing more than 60% to the national Gross Domestic Product (GDP) and employing nearly 97% of the workforce. Within the creative economy sector, many MSMEs produce handmade and environmentally friendly products that are marketed through artisanal market communities. These markets function not only as spaces for economic exchange but also as platforms for interaction between producers and consumers, enabling artisans to communicate the values, production processes, and stories behind their products. However, many artisan entrepreneurs still face limitations in effectively communicating the value of their products and building meaningful engagement with consumers. Addressing this issue requires strengthening literacy and capacity in interpersonal communication and product storytelling. This community service program was conducted in collaboration with the Pasar Regeng Yogyakarta community, which serves as a platform for creative MSMEs to market nature-based and handcrafted products. Yogyakarta, widely recognized as a cultural hub and a major tourism destination, boasts a dynamic creative ecosystem that offers strong potential for the development of artisanal markets. The program implemented mentoring and communication literacy activities focusing on interpersonal communication skills and effective product storytelling. The results indicate that participants gained a deeper understanding of the role of communication in marketing artisan products and reported increased confidence in engaging with consumers. Post-test findings further reveal improved participant capacity to apply interpersonal communication and storytelling techniques in articulating the value and uniqueness of their products.